Perspectives of human resource management in the Asia Pacific - Nankervis, Alan R.; Chatterjee, S. R. (Samir Ranjan) 1945-; Coffey, Jane (Human resource management series (Pearson Education), 2006)
Perspectives of Human Resource Management in the Asia Pacific compares and contrasts human resource management (HRM) functions across countries in the Asia-Pacific region with similar or dissimilar economic, social, political and industrial relations traditions and institutions.